Mortality in the populations of Danzig and the District of Danzig (“Regierungsbezirk Danzig”) in the second half of the nineteenth century - Budnik, Alicja; Liczbińska, Grażyna (Anthropological Review, 1997)
The study concerning the populations of: the city of Danzig, Kartuzy County and the whole District of Danzig (Regierungsbezirk Danzig) has been based on demographic data from German yearbooks published in the second half of the nineteenth century and at the beginning of the twentieth century. The research has covered the period between 1855 and 1879 for the city of Danzig and between 1860 and 1869 for the District of Danzig. For selected years some demographic measures, such as: death rates, infant death rates, natural increase, and population dynamics rates have been estimated. At the same time, seasonal fluctuations in mortality within a year and the most important cultural and biological causes for death have been disscussed. Moreover, life tables for the whole District of Danzig have been built. (The authors employed two methods: firstly - Hailey’s proposal, assuming at first a stationary type of population and then a model stable in regard to formerly calculated natural increase; secondly - a technique based on probability of death). Finally, the opportunity for natural selection through differential mortality has been estimated (Crow index Im, potential gross reproduction rate Rp«, biological state index lb,). The results of the own research have been compared to attainable data concerning other regions of Poland under partition.